Sustainable Energy Economic Policy: Population, Energy Consumption, and Macroeconomic Conditions - Priyadi U.; Atmadji E.; Artiani L.E.; Nordin S.M.; Abdullah M.R.T.L.; Imron M.A.; Wildan M.A.; Omar R.C. (Econjournals, 2023)
This study examines and analyzes the energy economic policy of Indonesia with population, energy consumption and its macroeconomic condition in the short-run and long-run. In the long run, this study found that the non-renewable energy will be replaced with renewable energy. One of Indonesia's imported energy commodities is fuel and engine oil consumer goods. Based on the unit root test results, the Autoregressive Distributed Lag (ARDL) Model is the most appropriate model used in this study. The coefficient of determination indicated by the R-squared is 0.967579, which means the model can explain 96.8% of the international trade and its macroeconomic factors on the volume of imported fuel and engine oil in Indonesia. This study uses independent variables like total population, vehicle volume, gross domestic product (GDP), exchange rates, and foreign exchange reserves. These variables were fruitful in explaining the critical factors in the imported volume of fuel and engine oil, which are essential public goods used in daily activities and have to meet the people's consumption. In addition, the result reveals that the interesting thing is in the long run, the total population negatively affects fuel and engine oil imports in Indonesia. 2022, Econjournals. All rights reserved.